Effectiveness of Educational Intervention based on Protection Motivation Theory to Promotion of Preventive Behaviors from Brucellosis among Ranchers of Farmer - Somayeh Soleimanpour hossein abadi; Ali Mehri; Sedigheh Rastaghi; Masoumeh Hashemian; Hamid Joveini; Mohammad Hassan Rakhshani; Reza Shahrabadi (Hamadan University of Medical Sciences, 2021)
Aims: Brucellosis is one of the most important public health problems in developing countries, especially in rural areas closely related to animals. This study determines the effectiveness of an educational intervention based on Protection Motivation Theory on promoting preventive behaviors from brucellosis between the farmer's ranchers in the comprehensive rural health center. Materials & Methods: In this quasi-experimental study, 110 ranchers of the farmer (in two groups of intervention and control) were selected by two-stage cluster sampling. The data collection instrument was a researcher-made questionnaire consisting of two parts; the first part included demographic questions, and the second part related to knowledge of the disease and the Protection Motivation Theory questions. The data were analyzed by SPSS 16 using Mann Whitney, Shapiro-Wilk, Kruskal-Wallis, Regression, Fisher's Exact Test, and Chi-Square. Findings: After the educational intervention, awareness and all protection motivation theory structures in the intervention group compared to the control group have increased significantly (p<0.05). Also, the structures of protection motivation theory predicted 0.66% of the variance of preventive behaviors, and among them, self-efficacy and motivation related to behavior were the strongest predictors. Conclusion: This study confirms the effectiveness of an educational intervention based on the Protection Motivation Theory on adopting brucellosis's preventive behaviors.